(untitled) (Estudios humanísticos. Geografía, historia y arte, 1990)
The death penalty was a repression method used extensively in the First Roman Empire, for all kinds of social classes. This essay analyses, from a historical view, the various methods of death sentence used; and it is based on legislation or the age and mainly on latin writers.